Genetics of chronic post-surgical pain: a crucial step toward personal pain medicine = Génétique de la douleur chronique post chirurgicale : une étape cruciale vers une médecine personnalisée de la douleur - Clarke, Hance; Flor, Herta; Rietschel, Marcella (Canadian journal of anesthesia, 2014)
Purpose: Most patients who undergo surgery or experience a traumatic injury suffer from acute pain that subsides once tissues heal. Nevertheless, the pain remains in 15-30% of patients, sometimes for life, and this chronic post-surgical pain (CPSP) can result in suffering, depression, anxiety, sleep disturbance, physical incapacitation, and an economic burden. The incorporation of genetic knowledge is expected to lead to the development of more effective means to prevent and manage CPSP using tools of personalized pain medicine. The purpose of this review article is to provide an update on the current state of CPSP genetics and its future potential. Principle findings: The large variability in CPSP amongst patients undergoing similar surgery suggests that individual factors are significant contributors to CPSP, raising the possibility that CPSP is influenced by genetic determinants. Heritability estimates suggest that about half of the variance in CPSP levels is attributable to genetic variation. These estimates suggest that identifying the genetic underpinnings of CPSP may lead to significant improvements in treatment. Analyzing patients’ DNA sequences, blood and salivary pain biomarkers, as well as their analgesic responses to medications will facilitate developing insights into CPSP pathophysiology and inform predictive algorithms to determine a patient’s likelihood of developing CPSP even prior to surgery. These algorithms could facilitate effective treatment regimens that will protect against the transition to chronicity in traumatically injured patients or those scheduled for surgery and lead to better therapy for patients who have already developed CPSP. Conclusions: Pharmacogenomic technologies and strategies provide an opportunity to expand our knowledge in CPSP treatment that may manifest in a personalized approach to diagnosis, prevention, and therapy. Capitalizing on this genomic knowledge will necessitate the analysis of many tens of thousands of study patients. This will require an international coordinated effort to which anesthesiologists and surgeons can contribute substantially.